Proposed intelligence systems based on digital Forensics : Review paper - Ismael Sahib, Hussein; Alsudani, Mustafa Qahtan; Ali, Mohammed Hasan; Qassim Abbas, Haydar; Moorthy, Kohbalan; Adnan, Myasar Mundher (Elsevier Ltd, 2023)
The field of information security, in general, has seen shifts a traditional approach to an intelligence system. Moreover, an increasing of researchers to focus on propose intelligence systems and framework based on the forensic case studies because of the limitations of traditional methods such as analysis intensive data manually, intelligence visualization to make the evidence more understandable and intelligence system for store data. However, most of these intelligence systems are still facing different limitations. Furthermore, the primary goal of this work analysis popular intelligence system that was used based on forensic. Moreover, propose new algorithms and hybrid model which it's achieved good results in dif-ferent other fields to develop the forensic systems in the future.